A systematic review and meta-analysis of genotype–phenotype associations in patients with hypertrophic cardiomyopathy caused by sarcomeric protein mutations. Issue 24 (14th May 2013) - Lopes, Luís R; Rahman, M Shafiqur; Elliott, Perry M
Abstract : Background: The genetic basis of familial hypertrophic cardiomyopathy (HCM) is well described, but the relation between genotype and clinical phenotype is still poorly characterised. Objective: To summarise and critically review the current literature on genotype–phenotype associations in patients with HCM and to perform a meta-analysis on selected clinical features. Data sources: PubMed/Medline was searched up to January 2013. Retrieved articles were checked for additional publications. Selection criteria: Observational, cross-sectional and prospectively designed English language human studies that analysed the relationship between the presence of mutations in sarcomeric protein genes and clinical parameters. Data extraction and analysis: The pooled analysis was confined to studies reporting on cohorts of unrelated and consecutive patients in which at least two sarcomere genes were sequenced. A random effect meta-regression model was used to determine the overall prevalence of predefined clinical features: age at presentation, gender, family history of HCM, family history of sudden cardiac death (SCD), and maximum left ventricular wall thickness (MLVWT). The I 2 statistic was used to estimate the proportion of total variability in the prevalence data attributable to the heterogeneity between studies. Results: Eighteen publications (corresponding to a total of 2459 patients) were selected for the pooled analysis. The presence of any sarcomere gene mutation was associated with a younger age at presentation (38.4 vs 46.0 years, p<0.0005), a family history of HCM (50.6% vs 23.1%, p<0.0005), a family history of SCD (27.0% vs 14.9%, p<0.0005) and greater MLVWT (21.0 vs 19.3 mm, p=0.03). There were no differences when the two most frequently affected genes, MYBPC3 and MYH7, were compared. A total of 53 family studies were also included in the review. These were characterised by pronounced variability and the majority of studies reporting on outcomes analysed small cross-sectional cohorts and were unsuitable for pooled analyses. Conclusions: The presence of a mutation in any sarcomere gene is associated with a number of clinical features. The heterogeneous nature of the disease and the inconsistency of study design precludes the establishment of more precise genotype–phenotype relationships. Large scale studies examining the relation between genotype, disease severity, and prognosis are required.